2013
DOI: 10.1016/j.pscychresns.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced white matter integrity in the cingulum and anterior corona radiata in posttraumatic stress disorder in male combat veterans: A diffusion tensor imaging study

Abstract: Posttraumatic stress (PTSD) and alcohol use (AUD) disorders are associated with abnormal anterior cingulate cortex/ventromedial prefrontal cortex, thalamus, and amygdala function, yet microstructural white matter (WM) differences in executive-limbic tracts are likely also involved. Investigating WM in limbic-thalamo-cortical tracts, this study hypothesized (1) fractional anisotropy (FA) in dorsal cingulum, parahippocampal cingulum, and anterior corona radiata (ACR) would be lower in individuals with comorbid P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 67 publications
(113 reference statements)
7
102
1
Order By: Relevance
“…In contrast, previous studies have reported decreased cingulum FA of PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011). These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, previous studies have reported decreased cingulum FA of PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011). These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls.…”
Section: Discussionmentioning
confidence: 71%
“…FA is a measure sensitive to alterations in axonal directionality and white matter organization (Beaulieu, 2009). Reduced FA in the cingulum bundle has frequently been reported in PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011), although heightened FA in the cingulum bundle has also been reported (Abe et al, 2006;Zhang et al, 2012). One longitudinal study has investigated white matter microstructure in a small sample of only eight PTSD patients, 10 and 24 months after experiencing a traumatic event ).…”
Section: Introductionmentioning
confidence: 99%
“…Other reasons for the failure to replicate may be related to FA changes over the course of the illness. There is mounting evidence of increased FA early in the course of illness [9,12,17,47], and reduced FA in chronic or complex PTSD (often featuring comorbid depression, brain injury, or alcohol use disorder) [10,11,15,16,19,48]. Homogenous samples with early onset or highly chronic cohorts might be more successful at demonstrating a relationship between PTSD and FA.…”
Section: Discussionmentioning
confidence: 99%
“…Although other regions of interest (ROI) have been implicated, analyses using DTI and tractography have most consistently demonstrated microstructural alterations of the cingulum and the uncinate fasciculus (UNC) in PTSD [9][10][11][12][13][14][15][16][17][18][19]. However, there have been inconsistencies in the literature in the directionality and extent of alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The ACR is well known to be a part of the limbic-thalamocortical circuitry which plays an important role in emotional regulation and which is involved in the pathophysiology of MDD (Drevets et al, 2008;Sanjuan et al, 2013). Several studies have found that the microstructural integrity of the ACR modulates executive attentional networks related with attention-mediating inhibitory control and resolution of cognitively-incongruent stimuli (Niogi et al, 2010;Yin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%